Turning Waste into Nutrition: Harnessing Tannery Waste for Black Soldier Fly Larvae Cultivation as Sustainable Catfish Feed Alternatives - Yuliatmo, Ragil; Maharani, Sakti; Nurbalia, Elis; Wibowo, Raden Lukas Martindro Satrio Ari (International Journal of Agriculture System, 2024)
This study aimed to help reduce the lime fleshing solid waste problem by implementing utilization as feed for Black Soldier Fly (BSF) larvae. The BSF larvae were analyzed as a sample to determine whether it is safe to be eaten by other living species, especially catfish. The raw material used is lime fleshing cowhide waste from a leather tannery. The process included fermentation of lime fleshing waste with a formulation of waste: bran: water (8:1:2) for three days, hatching BSF larvae eggs for six days, and feeding fermented waste to BSF larvae (1000:1) for nine days, then baby BSF larvae dried, and BSF larvae were applied to catfish in a ratio (BSF larvae weight = 9: 5) for 12 days. Then, they analyzed the protein, calcium, and sulfur contents on the sample BSF larvae and catfish. We used the fermentation of lime fleshing waste with bran and water variables, which are well water, catfish pond water, and rice washing water, for three days. Then, hatching BSF larvae eggs for six days, BSF larvae cultivation for nine days, and application of the BSF larvae on catfish for 12 days. Data were analyzed by one-way ANOVA, then continued using the Duncan Multiple Range Test (DMRT). The result of fermented lime fleshing waste was used on the BSF larvae, and the cultivation contents were analyzed for protein, calcium, and sulfur. The analysis result of the three variables has an average value of protein at around 6.06%, calcium at 0.041%, and sulfur at around 0.016%. The study concludes that BSF larvae, when combined with commercial feed and suitable formulation, could be an effective and efficient alternative feed for catfish while addressing the lime fleshing waste problem.